From Brown to Grutter: The Legal Struggle for Racial Equality - Theodore M. Shaw (Washington University Journal of Law & Policy, 2004)
This paper addresses the historical developments in the legal struggle for racial equality. Examining several cases including Brown v. Board of Education and Grutter v. University of Michigan, the essay documents the progresses and failures of racial equality in the last fifty years.
Keywords: School integration; Affirmative action programs in education; Civil rights -- Consitutional history; Brown v. Board of Education; Grutter v. Bollinger